Rearrest during hospitalisation in adult comatose out-of-hospital cardiac arrest patients: Risk factors and prognostic impact, and predictors of favourable long-term outcomes. (January 2022) - Jung, Yong Hun; Jeung, Kyung Woon; Lee, Hyoung Youn; Lee, Byung Kook; Lee, Dong Hun; Shin, Jonghwan; Lee, Hui Jai; Cho, In Soo; Kim, Young-Min
Abstract: Background: Rearrest occurs commonly after initial resuscitation following out-of-hospital cardiac arrest (OHCA). We determined (1) the predictors of rearrest during hospitalisation that can be identified in the hours immediately after OHCA, (2) the association between rearrest and favourable long-term outcomes, and (3) the predictors of favourable long-term outcomes in rearrest patients. Methods: Conditional multivariable logistic regression analyses were performed using the Korean Hypothermia Network prospective registry data, which included details of adult OHCA patients treated with targeted temperature management at 22 teaching hospitals in South Korea. Results: Among the 1, 233 patients, 260 (21.1%) experienced rearrest. Of the 192 patients resuscitated from first rearrest, 33 (17.2%) achieved 6-month favourable outcomes. Arrhythmia, heart failure, ST-segment elevation, lower initial Glasgow coma scale (GCS) motor score, higher initial lactate level, and antiarrhythmic drug use within 1 h were independently associated with rearrest. Higher lactate level and antiarrhythmic drug use were associated with shockable first rearrest, while arrhythmia, heart failure, ST-segment elevation, and lower GCS motor score were associated with non-shockable first rearrest. Rearrest was independently associated with a lower likelihood of 6-month favourable outcomes (P = 0.003). Initial shockable rhythm after OHCA, absence of diabetes, shorter cumulative time to restoration of spontaneous circulation, coronary angiography, and hypophosphataemia within 7 d were independently associated with 6-month favourable outcomes in the patients resuscitated from first rearrest. Conclusions: Rearrest during hospitalisation after OHCA was inversely associated with 6-month favourable outcomes. We identified several risk factors for rearrest and prognostic factors for patients resuscitated from first rearrest.